2019
DOI: 10.1002/hep.30363
|View full text |Cite
|
Sign up to set email alerts
|

Orchestration of Tryptophan‐Kynurenine Pathway, Acute Decompensation, and Acute‐on‐Chronic Liver Failure in Cirrhosis

Abstract: Systemic inflammation (SI) is involved in the pathogenesis of acute decompensation (AD) and acute‐on‐chronic liver failure (ACLF) in cirrhosis. In other diseases, SI activates tryptophan (Trp) degradation through the kynurenine pathway (KP), giving rise to metabolites that contribute to multiorgan/system damage and immunosuppression. In the current study, we aimed to characterize the KP in patients with cirrhosis, in whom this pathway is poorly known. The serum levels of Trp, key KP metabolites (kynurenine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 36 publications
4
75
0
2
Order By: Relevance
“…Finally, a number of metabolites with well-known effects on the immune system, such as those belonging to the tryptophan–kynurenine pathway, mostly circulate bound to albumin. Therefore, their free serum levels in decompensated cirrhosis can be increased due to hypoalbuminaemia, structural changes of albumin or binding competition with endogenous and exogenous substances 63…”
Section: The Concept Of Albumin As a Drugmentioning
confidence: 99%
“…Finally, a number of metabolites with well-known effects on the immune system, such as those belonging to the tryptophan–kynurenine pathway, mostly circulate bound to albumin. Therefore, their free serum levels in decompensated cirrhosis can be increased due to hypoalbuminaemia, structural changes of albumin or binding competition with endogenous and exogenous substances 63…”
Section: The Concept Of Albumin As a Drugmentioning
confidence: 99%
“…Liver failure shares many similarities with sepsis with regard to acute inflammation and development of immunoparalysis [26]. Systemic inflammation may be involved in the pathogenesis of ACLF and be a prognostic factor for evolution towards ACLF in patients with acutely decompensated cirrhosis [27,28]. Although not analysed in detail, presence of comorbidities in our cohort was associated with all outcomes, but 28-day mortality.…”
Section: Table 2 Risk Factors For Liver Transplantation (N = 22) Versmentioning
confidence: 78%
“…The kynurenine pathway for tryptophan catabolism mainly occurs in the liver; however, tryptophan level varies depending on liver function and availability of the rate-limiting enzyme (indoleamine 2,3-dioxygenase) induced by inflammatory response and kidney function 28 . A recent prospective study revealed that, in the 70% resection model with compensated liver function, serum tryptophan level increased with normal or mildly elevated indoleamine 2,3-dioxygenase level 29 . Conversely, in the 90% resection model with decompensated liver function, tryptophan level decreased with increase in indoleamine 2,3-dioxygenase level induced by other organs such as the kidney 29 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study revealed that, in the 70% resection model with compensated liver function, serum tryptophan level increased with normal or mildly elevated indoleamine 2,3-dioxygenase level 29 . Conversely, in the 90% resection model with decompensated liver function, tryptophan level decreased with increase in indoleamine 2,3-dioxygenase level induced by other organs such as the kidney 29 . Given the similar inflammatory states in the 70% and 90% resection models, it is unclear if compensation determines the tryptophan level 26,27,29 .…”
Section: Discussionmentioning
confidence: 99%